Vegetation structure and floristic composition of Gergeda Anfillo Forest, West Ethiopia - Raga, Dessalegn; Seid, Ali (Ethiopian Journal of Science and Technology, 2025)
Ethiopia is a tropical country with tropical, subtropical and temperate types of vegetations. However, many vegetation types are not described and characterized. The aim of this study was to assess the floristic composition and structure of the protected Gergeda Anfillo Forest vegetation. The forest was located in Kellem Wollega Zone, southwestern Ethiopia. Stratified sampling method was used for vegetation data collection. Samples were taken from 40 quadrats of 20 m x 20 m (for woody species) that were laid along transect laid about 200 m apart. 120 subplots (1 m x 1 m) were used for herbs in the main plots. A total of 134 (11 endemic) species, 116 genera, and 61 families were recorded. The five most dominant tree species with highest importance value index were Schefflera abyssinica, Ekebergia capensis, Albizia gummifera, Croton macrostachyus, and Olea welwitschii. The most abundant families were Fabaceae (14 species), Poaceae (11 species), Asteraceae (10 species), and Euphorbiaceae (7 species). Moreover, the forest housed 10 of the 24 national priority tree species and four plant communities were identified by cluster analysis. Structural analysis revealed that the forest is dominated by small sized trees and shrubs. This indicates that the forest is facing selective cutting and/or it is in secondary stage regeneration. Given the non-seasonal climate, less differentiated communities, and high plant diversity, it is possible to conclude that the forest can be categorized as tropical rainforests of western Ethiopia. Thus, protection of the forest is highly recommended.